PENGARUH OPERASIONAL KAPAL ANCHOR HANDLING TOWING SUPPLY HARRIER TERHADAP KINERJA OPERASIONAL PHEONWJ - Marthaleina Rumindang Sitorus; Kusno Wibowo (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2014)
The object of this research is PT Baruna Raya Logistics in Jakarta. This company operates the ships main service which provides logistic support for offshore exploration, drilling, construction, production, and other activities related to offshore petroleum and mining industries. The company also develops business related to the boats’ crew, anchor handling vessel and supply vessel. This study conducted to know the effect of Anchor Handling Towing Vessel operating Harrier Supply to the performance of PHEONWJ PT Baruna Raya Logistics in Jakarta. The researchers use the linear regression method and look for correlation of the research object. From the data processing can be seen that there is a significant effect on the operation of a ship Anchor Handling Towing Supply PHEONWJ Harrier of performance. The influence of these two variables is significant which can be seen from the results of hypothesis: t-count> t-table or 3.384> 1.701.